Delayed intramural duodenal hematoma after a simple diagnostic endoscopic ultrasonography fine-needle aspiration procedure - Roseira, Joana (2019)
A 65-year-old man was evaluated for a difficult-to-characterize pancreatic head mass in the setting of idiopathic chronic pancreatitis. He had no other relevant medical history and was not taking any anticoagulant or antiplatelet treatment. Endoscopic ultrasonography fine-needle aspiration (EUS-FNA) failed to reveal neoplasm cells. A linear array echoendoscope (Olympus GF-UCT140, Center Valley, PA) was advanced up to the duodenal bulb, from which the head of the pancreas was visualized. After ensuring a vessel-free access to the pancreatic parenchyma, the FNA was performed using a 22G needle (Slimline 22G Handle Needle; Boston Scientific, Marlborough, MA) with a total of 3 passes (Figure 1). Three weeks after this procedure, the patient was admitted for hematemesis preceded by vomiting. On admission, his general physical examination was unremarkable except for jaundice. His blood tests showed no anemia; his platelet count, prothrombin time, amylase, and liver enzymes were within normal range, but his total bilirubin level was elevated (7.4 mg/dL). Upper gastrointestinal endoscopy showed Mallory-Weiss tears, an evident extrinsic compression of the knee, and the second portion of the duodenum, which could not be passed by the endoscope. The investigation by computed tomography and magnetic resonance cholangiopancreatography led to the diagnosis of an 11-cm intramural duodenal hematoma (IDH), leading to both gastric outlet and main biliary duct obstruction (Figure 2). The case was successfully managed with nasogastric decompression and exclusive parenteral feeding. Symptoms improved within 15 days, and cholestasis progressively disappeared.